Effects of the degree of oral processing on the properties of saliva-participating emulsions: using stewed pork with brown sauce as the model - Mingcheng Zhang; Xiaocao Zhao; Dengyong Liu; Guan Wang (Food Science and Human Wellness)
This work investigated the changes in properties of saliva-participating emulsions during different oral processing stages (the whole process from intake to swallowing was divided into five stages, i.e., 20 %, 40 %, 60 %, 80 % and 100 % stage). The stewed pork with brown sauce was masticated and the emulsion was collected for the determination of emulsion stability, droplet size, ζ-potential, interfacial tension, and microstructure. The results showed that the emulsion stability increased gradually during the oral processing and reached the highest level near the swallowing point. The droplet size of emulsion showed a significant downward trend (P < 0.05). Microstructure observations also found different degrees of reduction in fat droplets size at different stages of oral processing. In addition, the ζ-potential of food boluses emulsion was decreased from −16.4 mV to −41.2 mV and the interfacial tension decreased by 52.6 % before and after oral progressing. In conclusion, the oral processing of stewed pork with brown sauce was essentially a process in which fat was constantly emulsified, and saliva might act as an emulsifier. This study provides new insights on understanding the oral processing process and sensory changes of fat.